LEVEL ESTIMATION OF BLOOD SATURATION AT PATIENTS WITH CHRONIC KIDNEY DISEASE ON THE PROGRAM HEMODIALYSIS - LysyanskaО. U. (Ukrainian Journal of Nephrology and Dialysis, 2017)
Patients with chronic kidney disease, who are on outpatient program of hemodialysis treatment, have a risk of development of intradialysis chronic hypoxemia (hypoxemia, that appears during the hemodialysis), that appears during the program dialysis treatment. Aim: identifying of patients with Chronic kidney disease with decrease of the percentage oxyhemoglobin content in arterial blood during hemodialysis. Materials and Methods. Participated 91 patients with Chronic kidney disease on the program hemodialysis, who were monitored under the non-invasive method of pulsoximetry of blood saturation. Results. During the research was found that the first group of patients with initial normal medical parameters (SpO2 within the normal range 95-99%) consisted 57 patients (62,6% from the general quantity); to the second group (SpO2 within 90-94%) (including,16 patients, medical parameters of whom were changed with time) belonged 21 patients (23,1%); to the third group (SpO2 range less than 90%) belonged 14 patients (15,4%) (13 of whom came to third group from second and one person got into this group with the previously normal medical parameters). Conclusion. Part of the patients on program hemodialysis may occur the blood saturation fluctuation, with exposure of hypoxemia conditions, that may worsen the prognosis and increase the complication of the disease.